2014
DOI: 10.4238/2014.september.26.11
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and relationship of chicory (Cichorium intybus L.) using sequence-related amplified polymorphism markers

Abstract: Chicory is a crop with economically important roles and is cultivated worldwide. The genetic diversity and relationship of 80 accessions of chicories and endives were evaluated by sequence-related amplified polymorphism (SRAP) markers to provide a theoretical basis for future breeding programs in China. The polymorphic rate was 96.83%, and the average polymorphic information content was 0.323, suggesting the rich genetic diversity of chicory. The genetic diversity degree of chicory was higher (G S = 0.677) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Kiers et al [ 7 ] studied endive and chicory cultivars using diagnostic AFLP markers in Cichorium species. Our results are in general agreement with several previous studies [ 28 , 29 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Kiers et al [ 7 ] studied endive and chicory cultivars using diagnostic AFLP markers in Cichorium species. Our results are in general agreement with several previous studies [ 28 , 29 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 94%
“…The genetic identification and differentiation of a taxon are applied in various species such as Brassica [ 24 ], broccoli and cauliflower [ 25 ], lettuce and Jew’s mallow [ 26 ], and tomato [ 27 ]. In Cichorium , various molecular markers were applied [ 7 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Some of these markers have been used for genetic map construction [ 31 , 32 ], genetic variation [ 33 , 34 ], gene flow [ 35 ], population structure [ 37 ], and hybridization [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…For each species, twelve genotypes were selected, including six genotypes with low (wild or landrace) and six with high (cultivar, inbred lines) level of improvement (Table S2). The genotypes were chosen based on description of domestication status, and phylogeny for each species (Blackman et al, 2011, Walley et al, 2017, Lin et al, 2014, Dempewolf et al, 2008, Bird et al, 2017, Liang et al, 2014, Valliyodan et al, 2016. Landrace genotypes were selected for C. endivia for which no wild relative is known and two B. rapa genotypes (Fig.…”
Section: Plant Materials and Growth Conditionmentioning
confidence: 99%
“…The similarity dendrogram showed that the analysed specimens constituted a fairly homogeneous group with high similarity values (about 85%), with the exception of samples RS1, RS9, and RS10. Genetic variability is affected by a number of factors including out-crossing mechanisms, environment, and natural or artificial selection [42]. In fact, Azevedo et al [43] reported that the genetic variation distribution of escarole is not random within populations and is determined by the reproductive system, geographic distribution, effective scale of populations, pattern of reproduction, gene flow through the spread of pollen, and evolutionary factors [44].…”
Section: Discussionmentioning
confidence: 99%